2016
DOI: 10.1021/acs.est.6b04633
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Suitability of Multiple Dispersion and Land Use Regression Models for Urban Traffic-Related Ultrafine Particles

Abstract: Comparative evaluations are needed to assess the suitability of near-road air pollution models for traffic-related ultrafine particle number concentration (PNC). Our goal was to evaluate the ability of dispersion (CALINE4, AERMOD, R-LINE, and QUIC) and regression models to predict PNC in a residential neighborhood (Somerville) and an urban center (Chinatown) near highways in and near Boston, Massachusetts. PNC was measured in each area, and models were compared to each other and measurements for hot (>18 °C) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…An increasing number of studies use mobile monitoring to characterize specific traffic corridors, develop and assess empirical models, and apply those models for epidemiological studies . Use of mobile monitoring may be particularly useful for pollutants with high spatial and temporal variability .…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies use mobile monitoring to characterize specific traffic corridors, develop and assess empirical models, and apply those models for epidemiological studies . Use of mobile monitoring may be particularly useful for pollutants with high spatial and temporal variability .…”
Section: Introductionmentioning
confidence: 99%
“…A few recent studies have evaluated the RLINE model output for various pollutant concentrations. However, these studies have either just visually compared observed concentrations versus the RLINE model output (Saha, Khlystov, Snyder, & Grieshop, ) or compared the correlation between the RLINE model output against various forms of observed concentrations: across regional air quality monitors (Milando & Batterman, ; Yu et al, ) or smoothed averages based on MAPL measurements (Patton, Milando, Durant, & Kumar, ). They do not attempt to quantify the potential biases in the RLINE model output.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the differences in population, traffic flow and human activities between the functional areas, the mass of build-up particles on the road, the metal concentration and the emission factors of road dust were different (Liu et al, 2019;Patton et al, 2017).…”
Section: -3 Figs S3mentioning
confidence: 99%